1992
DOI: 10.1089/cap.1992.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Megavitamin Treatment of Mental Retardation in Children: A Review of Effects on Behavior and Cognition

Abstract: Many forms of vitamin supplementation have been proposed for the treatment of behavioral and cognitive disorders in children with mental retardation. Except for nutrient deficiencies and selected inborn errors of metabolism, the efficacy of these treatments has not been established. Therapeutic supplementation with vitamin B(6) in Down syndrome and folie acid in fragile X syndrome was attempted following the identification of apparent biochemical aberrations involving the nutrients. Double-blind controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In 1981, Harrell et al [211] reported that the administration of a megavitamin mineral supplement to a heterogenous group of 16 mentally retarded children, 4 of which had DS, had led to encouraging results. However, controlled double-blind studies on somewhat larger groups using similar megadoses of vitamins and minerals but no thyroid supplementation did not result in any beneficial effects [212][213][214][215][216]. However, these studies were devoid of a detailed theory of the mechanism of action, and the age distribution of the patients was disadvantageous in relation to possible targets in the developing brains.…”
Section: Advances In the Development Of Novel Antioxidant Therapiesmentioning
confidence: 99%
“…In 1981, Harrell et al [211] reported that the administration of a megavitamin mineral supplement to a heterogenous group of 16 mentally retarded children, 4 of which had DS, had led to encouraging results. However, controlled double-blind studies on somewhat larger groups using similar megadoses of vitamins and minerals but no thyroid supplementation did not result in any beneficial effects [212][213][214][215][216]. However, these studies were devoid of a detailed theory of the mechanism of action, and the age distribution of the patients was disadvantageous in relation to possible targets in the developing brains.…”
Section: Advances In the Development Of Novel Antioxidant Therapiesmentioning
confidence: 99%
“…Vitamin supplementation has been proposed for numerous behavioral and cognitive disorders in children with mental retardation. A review of the literature has shown that vitamin B6 was ineffective in treating children with Down syndrome, folic acid treatment had very limited effects on some children with fragile X syndrome, megadose multivitamin supplements have not been effective with cognitive disorders or attention-deficit disorders, and multivitamins and minerals have not been effective with Down syndrome or other forms of mental retardation (Kozlowski, 1992). To judge the efficacy of diets requires an examination of the primary sources (i.e., the original studies), but the controversy has arisen because of people's interpretations of the pros and cons of a practice.…”
Section: Medicalmentioning
confidence: 99%